一种致密油气藏压裂水平井变制度生产动态模拟监测方法 (2024)
本发明公开了一种致密油气藏压裂水平井变制度生产动态模拟监测方法，具体涉及石油天然气开采技术领域。本发明基于致密油气藏的现场数据，划分生产阶段后，利用致密气藏五线性流模型进行反演模拟获取未知参数组中各参数的最优值后，再建立生产制度转换模型，结合致密油气藏的现场数据和未知参数组反演结果，利用致密气藏五线性流模型模拟日产量并进行拟合，得到压裂水平井日产量预测模型并验证其准确性后，通过时间积分得到压裂水平井累计产量预测模型，将压裂水平井日产量预测模型和压裂水平井累计产量预测模型用于产能预测。本发明方法有效克服了传统复合线性流解析方法模拟监测精度不足的问题，计算效率高，为后续生产制度优化调整提供了依据。 The invention discloses a compact oil and gas reservoir fractured horizontal well variable system production dynamic simulation monitoring method, and particularly relates to the technical field of oil and gas exploitation. The method comprises the following steps: dividing production stages based on field data of the tight oil and gas reservoir, performing inversion simulation by using a tight gas reservoir five-linear flow model to obtain the optimal value of each parameter in an unknown parameter group, establishing a production system conversion model, and combining the field data of the tight oil and gas reservoir and the inversion result of the unknown parameter group to obtain the optimal value of each para